2022
DOI: 10.3390/ph15070856
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, In Vitro and In Vivo Evaluation of Non-Ordered Mesoporous Silica-Based Ternary Solid Dispersions for Enhanced Solubility of Flurbiprofen

Abstract: The aim of this study was to improve the solubility and prevent the ulcerogenic effect of flurbiprofen. Initially, binary and ternary solid dispersions (BSDs and TSDs) of flurbiprofen were prepared by using non-ordered mesoporous silica and gelucire. After preformulation testing (solubility, flow properties, % yield, and entrapment efficiency), four formulations were selected for further detailed studies. Solid-state characterization of optimized formulations (S1, S6, S7, and S12) showed successful drug incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…It was observed that free-flowing dispersions were obtained with lipid carriers up to 40%, beyond which a sticky and agglomerated mass was obtained, thus hindering processing. Similar trends have been reported for TSDs based on gelucire [ 27 ]. For hydrophilic carriers, drug solubility showed an increasing trend with a higher concentration of carrier, which may have been due to the improved wetting and solubilizing nature of surfactants [ 22 ].…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…It was observed that free-flowing dispersions were obtained with lipid carriers up to 40%, beyond which a sticky and agglomerated mass was obtained, thus hindering processing. Similar trends have been reported for TSDs based on gelucire [ 27 ]. For hydrophilic carriers, drug solubility showed an increasing trend with a higher concentration of carrier, which may have been due to the improved wetting and solubilizing nature of surfactants [ 22 ].…”
Section: Resultssupporting
confidence: 88%
“…In the case of S1, S18, and S23, the absorption peaks of Dex were shifted from 1697 to 1704.17, 1732.16, and 1732.09 cm −1 . This is possibly due to the weak interaction of Dex with the mesoporous surface, which is reversible in nature, as mentioned in the literature [ 27 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations